2017
DOI: 10.1186/s12889-017-4727-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and anthropometric characteristics among adolescents living in urban or rural areas of Kosovo

Abstract: BackgroundHigh physical fitness levels in childhood and adolescence are associated with positive health-related outcomes later in life. Albeit many researchers investigated rural-urban differences in physical fitness, the outcomes of these studies are inconsistent and data on Kosovo are widely missing. Thus, this study aims to examine anthropometric and physical fitness parameters in 14 to 15 year old Kosovan adolescents living in rural and urban areas.MethodsTwo schools from Pristina (mostly urban population)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 77 publications
6
25
1
4
Order By: Relevance
“…According to them (Marchi & Uzoniche 2010 in Olubayo-Fatiregun, Ayodele, & Olorunisola, 2014), engagement in physical activities prevents many diseases such as cardio-vascular and coronary artery disease, diabetes, obesity, and some forms of cancer. Emphasizing the association of physical activity and health, current research findings are consistent with the findings of other studies (Tishukaj, Shalaj, Gjaka, Ahmetxhekaj, Bachl, Tschan, 2017;Rendi, Szabo, Szabo, Velenczeei and Kovacs, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…According to them (Marchi & Uzoniche 2010 in Olubayo-Fatiregun, Ayodele, & Olorunisola, 2014), engagement in physical activities prevents many diseases such as cardio-vascular and coronary artery disease, diabetes, obesity, and some forms of cancer. Emphasizing the association of physical activity and health, current research findings are consistent with the findings of other studies (Tishukaj, Shalaj, Gjaka, Ahmetxhekaj, Bachl, Tschan, 2017;Rendi, Szabo, Szabo, Velenczeei and Kovacs, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, abdominal adiposity in combination with a poor PF are directly associated with serious diseases [77,78]. The association between body composition parameters (waist circumference, percentage of body fat, and BMI) and performance in numerous fitness tests has been extensively studied in Europe [79] and non-European countries [80,81], thus determining the need for preventive work and the monitoring of the health status of adolescents. If we examine the results of the tests of the AFB, a better performance can be observed among those participants with N-O waist , N-O fat , and N-O weight in the long jump, speed/agility, and cardiorespiratory resistance tests.…”
Section: Fitness Performance In Boys and Girls With And Without O Waimentioning
confidence: 99%
“…Some studies have shown higher PA and physical fitness levels in urban youth [27][28][29], while others have shown opposite results [2,30,31]. There is also research indicating limited differences in physical fitness by living environment [6,32,33]. These inconsistencies could be attributed to differences in the definition and criteria used to differentiate between urban and rural living environments, as well as the methodology used to assess PA and physical fitness.…”
mentioning
confidence: 99%